Evaluation of Bone Mineral Density in Children Conceived via Assisted Reproductive Technology - Xia, Xinru; Chen, Lingling; Wang, Jing; Yu, Xiang; Gao, Li; Zhang, Yuan; Diao, Feiyang; Cui, Yugui; Liu, Jiayin; Meng, Yan (Frontiers in Endocrinology, 2022)
Objectives: To investigate bone mineral density (BMD) differences between assisted reproductive technology (ART)-conceived children and naturally conceived (NC) children. Study design: This retrospective cohort study included ART-conceived children and controls aged 1 to 12 years assessed with a follow-up protocol. Maternal and paternal background, birth condition, and growth and development indicators were analyzed. Results: The ART and NC groups exhibited differences in maternal and paternal childbearing age; maternal weight; maternal body mass index (BMI); maternal alcohol consumption; paternal smoking; delivery method; and serum zinc, iron, and lead levels. Multifactor analysis adjusted for relevant factors showed that paternal childbearing age and group significantly affected the BMD Z score. In the subgroup analysis, in vitro fertilization (IVF) (p=0.026) or intracytoplasmic sperm injection (ICSI) (p=0.008) had a positive impact on the BMD Z score. Male infertility only (p=0.010) or male infertility combined with polycystic ovary syndrome (PCOS) (p=0.026) may affect the BMD Z score. In the embryo transfer cycle subgroup analysis, compared with natural conception, both stimulation cycle fresh embryo transfer (p=0.019) and natural cycle frozen embryo transfer (p=0.006) had a positive effect on the BMD Z score. Conclusions: The BMD levels of the ART and control groups were generally in the normal range. Paternal childbearing age and the use of ART independently affected the BMD Z score of the offspring.